Method for producing carbon nanotube dispersion
Patent Information
- Application Number
- JP2023131560
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0018】 本発明によれば、カーボンナノチューブが良好に分散されたカーボンナノチューブ分散液の製造方法を提供することができる。
Smart Images

Figure 2025026160000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a carbon nanotube dispersion liquid. [Background technology]
[0002] 2. Description of the Related Art Carbon nanotubes (hereinafter sometimes abbreviated as "CNTs") have been attracting attention as a material that has excellent properties such as electrical conductivity, thermal conductivity, and strength.
[0003] Although each CNT has excellent properties, it is easy for them to be bundled by van der Waals forces due to their small outer diameter. For this reason, it has been conventional to prepare a carbon nanotube dispersion (CNT dispersion) by dispersing CNTs in a solvent (dispersion medium). However, CNTs with small outer diameters have strong cohesive forces and are difficult to disperse, so it is generally difficult to obtain a CNT dispersion in which CNTs are well dispersed.
[0004] In recent years, therefore, various attempts have been made to improve the dispersibility of CNTs in solvents and to disperse CNTs well in the solvent. For example, Patent Document 1 considers dispersing CNTs in acetone while applying ultrasonic waves. Patent Document 2 also discusses dispersing CNTs in acetone while applying ultrasonic waves. (1) Patent Document 2 describes a method for dispersing CNTs in acetone that is more than 3 nm and less than 10 nm in average outer diameter, (2) a peak is present at a diffraction angle 2θ=25°±2° in powder X-ray diffraction analysis, and the half-width of the peak is 3° to 6°, and (3) a peak width of 1560 to 1600 cm in Raman spectrum is observed. -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within this range is defined as D, preparation of a CNT dispersion using CNTs having a G / D ratio of 0.5 to 4.5 and a dispersant is being considered. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2000-86219 A [Patent Document 2] International Publication No. 2020 / 004095 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the above-mentioned conventional techniques have room for improvement in terms of obtaining a carbon nanotube dispersion in which carbon nanotubes are well dispersed in a solvent.
[0007] Therefore, an object of the present invention is to provide a method for producing a carbon nanotube dispersion liquid in which carbon nanotubes are well dispersed. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems. The inventors have focused on the conditions for dispersing CNTs in a solvent. The inventors have newly discovered that when a mixture containing carbon nanotubes, a solvent, and a thickener is subjected to a dispersion process using a wet jet mill, if the pressure applied to the mixture and the number of times the mixture is passed through the wet jet mill (number of passes) satisfy certain conditions, a carbon nanotube dispersion in which carbon nanotubes are well dispersed in a solvent can be produced, and have completed the present invention.
[0009] That is, an object of the present invention is to advantageously solve the above problems, and according to the present invention, there are provided the following methods for producing a carbon nanotube dispersion liquid [1] to [5].
[0010] [1] A method comprising the steps of: subjecting a mixture containing carbon nanotubes, a solvent, and a thickener to a dispersion treatment using a wet jet mill; The pressure applied to the mixture in the dispersion treatment is 50 MPa or more; The method for producing a carbon nanotube dispersion liquid, wherein the number of passes in the dispersion treatment satisfies the relationship of the following formula (1): -0.15 × (pressure applied to the mixed liquid (MPa)) + 35 < number of passes < -1 × (pressure applied to the mixed liquid (MPa)) + 170 (1) In this way, when a mixture containing carbon nanotubes, a solvent, and a thickener is subjected to a dispersion process using a wet jet mill, if the pressure applied to the mixture and the number of times the mixture is passed through the wet jet mill (number of passes) satisfy the above-mentioned specified conditions, a carbon nanotube dispersion in which the carbon nanotubes are well dispersed in the solvent can be produced. In the present invention, the term "number of passes" refers to the number of times the entire amount of the mixed liquid passes through the wet jet mill.
[0011] [2] In the method for producing a carbon nanotube dispersion liquid according to the above [1], it is preferable that the number of passes in the dispersion treatment satisfies the relationship of the following formula (2). -0.2 x (pressure applied to the mixed liquid (MPa)) + 45 ≦ number of passes ≦ -0.9 x (pressure applied to the mixed liquid (MPa)) + 150 (2) In this way, if the number of passes in the dispersion treatment satisfies the above formula (2), the carbon nanotubes can be more satisfactorily dispersed in the obtained carbon nanotube dispersion while preventing the carbon nanotubes from being broken.
[0012] [3] In the method for producing a carbon nanotube dispersion according to the above [1] or [2], the number of passes in the dispersion treatment is preferably 60 or less. In this way, if the number of passes in the dispersion treatment is 60 or less, the carbon nanotubes can be more satisfactorily dispersed in the obtained carbon nanotube dispersion while preventing breakage of the carbon nanotubes.
[0013] [4] In any of the methods for producing a carbon nanotube dispersion according to the above [1] to [3], the pressure applied to the mixed liquid in the dispersion treatment is preferably 100 MPa or less. In this way, if the pressure applied to the mixed liquid in the dispersion treatment is 100 MPa or less, the carbon nanotubes can be more satisfactorily dispersed in the obtained carbon nanotube dispersion while preventing breakage of the carbon nanotubes.
[0014] [5] In any of the methods for producing a carbon nanotube dispersion according to the above [1] to [4], the content of the carbon nanotubes in the mixed liquid is preferably 0.4% by mass or more and 1.0% by mass or less. In this way, if the content of the carbon nanotubes in the mixed liquid is within the above range, the carbon nanotubes can be more satisfactorily dispersed in the resulting carbon nanotube dispersion, while the conductivity of a carbon film or the like produced using the carbon nanotube dispersion can be increased.
[0015] [6] In any one of the methods for producing a carbon nanotube dispersion according to the above items [1] to [5], the content of the thickener in the mixed liquid is preferably 0.4% by mass or more and 1.2% by mass or less. In this way, if the content of the thickener in the mixed liquid is within the above range, the carbon nanotubes can be more satisfactorily dispersed in the resulting carbon nanotube dispersion, while the conductivity of a carbon film or the like produced using the carbon nanotube dispersion can be increased.
[0016] [7] In any one of the methods for producing a carbon nanotube dispersion according to the above [1] to [6], the thickener is preferably carboxymethylcellulose or a salt thereof. By using carboxymethylcellulose or a salt thereof as the thickener, it is possible to obtain a carbon nanotube dispersion in which the carbon nanotubes are more favorably dispersed.
[0017] [8] In any of the methods for producing a carbon nanotube dispersion according to [1] to [7] above, the G / D ratio of the carbon nanotubes is preferably 0.5 or more and 120 or less. In this way, when the G / D ratio of the carbon nanotubes is within the above-mentioned predetermined range, the bundles can be unbundled, and the conductivity of a carbon film or the like produced using a carbon nanotube dispersion containing a large number of carbon nanotubes can be improved. In the present invention, the "G / D ratio" refers to the ratio of the G band peak intensity to the D band peak intensity in a Raman spectrum, and can be measured by the method described in the Examples. Effect of the Invention
[0018] According to the present invention, it is possible to provide a method for producing a carbon nanotube dispersion liquid in which carbon nanotubes are well dispersed. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a graph showing the relationship between the number of passes through a wet jet mill (vertical axis) and the pressure applied to the mixed liquid (horizontal axis) in an example and a comparative example in which the CNT concentration in the mixed liquid was 0.1 mass %. [Diagram 2] FIG. 2 is a graph showing the relationship between the number of passes through a wet jet mill (vertical axis) and the pressure applied to the mixed liquid (horizontal axis) in examples and comparative examples in which the CNT concentration in the mixed liquid was 0.2 mass %. [Diagram 3] FIG. 3 is a graph showing the relationship between the number of passes through a wet jet mill (vertical axis) and the pressure applied to the mixed liquid (horizontal axis) in an example and a comparative example in which the CNT concentration in the mixed liquid was 0.4 mass %. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail. The method for producing a CNT dispersion of the present invention can be used to produce a CNT dispersion. The CNT dispersion produced by the method for producing a CNT dispersion of the present invention can be suitably used as a material for forming, for example, a molded body such as a carbon film or an elastomer molded body, an electrode for a secondary battery, or the like.
[0021] (Method of manufacturing carbon nanotube dispersion) The method for producing a CNT dispersion of the present invention includes a step of dispersing a mixture containing CNTs, a solvent, and a thickener using a wet jet mill (dispersion step). The method for producing a CNT dispersion of the present invention is characterized in that the pressure applied to the mixture in the dispersion step is 50 MPa or more, and the number of passes in the dispersion step satisfies the relationship of the following formula (1). -0.15 × (pressure applied to the mixed liquid (MPa)) + 35 < number of passes < -1 × (pressure applied to the mixed liquid (MPa)) + 170 (1) The method for producing a CNT dispersion liquid of the present invention may include steps (other steps) other than the dispersion step described above. According to the method for producing a CNT dispersion of the present invention, a CNT dispersion in which CNTs are well dispersed can be obtained.
[0022] <Dispersion process> In the dispersion step, a mixture containing a plurality of CNTs, a solvent, a thickener, and optionally containing components other than the CNTs, the solvent, and the thickener (other components) is subjected to a dispersion treatment using a wet jet mill.
[0023] < <cnt>> The CNTs contained in the mixed liquid (CNTs used as a raw material when preparing the CNT dispersion liquid, hereinafter referred to as "raw CNTs") are not particularly limited, but preferably contain single-walled CNTs. Furthermore, as the raw CNTs, only single-walled CNTs may be used, or a combination of single-walled CNTs and multi-walled CNTs may be used.
[0024] [Characteristics of raw CNT] The average length of the raw material CNTs is preferably 1.5 μm or more, more preferably 2.0 μm or more, and is preferably 4.0 μm or less, more preferably 3.5 μm or less. If the average length of the raw material CNTs is within the above range, the CNTs can be more satisfactorily dispersed in the CNT dispersion liquid. The "average length" of the raw material CNTs can be determined by measuring the lengths of, for example, 20 CNTs on a scanning electron microscope (SEM) image and calculating the number-average value.
[0025] The average diameter of the raw material CNTs is preferably 2.0 nm or more, more preferably 2.5 nm or more, and is preferably 5.5 nm or less, more preferably 5.0 nm or less. If the average diameter of the raw material CNTs is within the above range, the CNTs can be more satisfactorily dispersed in the CNT dispersion liquid. The "average diameter" of the raw material CNTs can be determined by measuring the diameter (outer diameter) of, for example, 20 CNTs on a transmission electron microscope (TEM) image and calculating the number average value.
[0026] Furthermore, the raw material CNTs preferably have a G / D ratio of 0.5 or more, more preferably 1 or more, and preferably 120 or less, more preferably 110 or less, even more preferably 95 or less, even more preferably 70 or less, even more preferably 45 or less, and particularly preferably 20 or less. If the G / D ratio of the raw material CNTs is within the above-mentioned range, the resulting bundles can be unbundled, and the conductivity of a carbon film or the like produced using a carbon nanotube dispersion liquid containing a large number of carbon nanotubes can be improved.
[0027] [Content percentage] The content of the raw CNT in the mixed liquid is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.4% by mass or more, preferably 2.0% by mass or less, and more preferably 1.0% by mass or less, based on 100% by mass of the total amount of the mixed liquid. If the content of CNT in the mixed liquid is within the above-mentioned range, the CNTs can be dispersed more satisfactorily in the obtained CNT dispersion liquid, while the conductivity of the carbon film or the like produced using the CNT dispersion liquid can be increased. Here, according to the method for producing a CNT dispersion of the present invention, even when the concentration of raw CNTs in the mixed liquid is high (for example, 0.4 mass% or more), the raw CNTs can be well dispersed, and a CNT dispersion in which the CNTs are well dispersed can be obtained.
[0028] [Synthesis method] The method for producing raw CNTs is not particularly limited, and examples thereof include a method using catalytic hydrogen reduction of carbon dioxide, an arc discharge method, a chemical vapor deposition method (CVD method), a laser evaporation method, a vapor phase growth method, a vapor phase flow method, and a HiPCO method. For example, the raw CNTs may be obtained by a method in which a trace amount of an oxidizing agent (catalyst activation material) is present in the system when a raw compound and a carrier gas are supplied onto a substrate having a catalyst layer for CNT production on the surface thereof to synthesize CNTs by the CVD method, thereby dramatically improving the catalytic activity of the catalyst layer (Super Growth Method; see International Publication No. 2006 / 011655). In addition, the raw CNTs may also be obtained by, for example, the eDIPS method, which is a type of vapor phase flow method.
[0029] <Solvent> The mixed liquid may contain only water as a solvent, may contain only an organic solvent (e.g., esters, ketones, alcohols) as a solvent, or may be a mixture of water and an organic solvent. From the viewpoint of dispersing CNTs in the CNT dispersion liquid more satisfactorily, the mixed liquid preferably contains water as a solvent. The mixed liquid may contain one type of organic solvent, or may contain two or more types of organic solvents.
[0030] The ratio of water in the solvent in the above-mentioned mixed liquid is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 99% by mass or more, and particularly preferably 100% by mass (i.e., the mixed liquid contains only water as a solvent), assuming the total amount of the solvent to be 100% by mass. If the ratio of water in the solvent in the mixed liquid is equal to or more than the lower limit, the conductivity of the molded body obtained by using the resulting CNT dispersion liquid can be further increased.
[0031] <Thickener> The thickener is not particularly limited, and any known thickener capable of assisting the dispersion of CNTs can be used. Examples of the thickener include water-soluble polymers such as cellulose-based polymers, polycarboxylic acids, and water-soluble vinyl polymers. Here, a polymer is "water-soluble" means that when 0.5 g of the polymer (solid content) is dissolved in 100 g of water at 25°C, the amount of insoluble matter is less than 10.0 mass %. The thickener may be used alone or in combination of two or more kinds in any ratio.
[0032] Examples of cellulose-based polymers include carboxymethylcellulose, methylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, and their salts and derivatives. Examples of polycarboxylic acids include polyacrylic acid, polymethacrylic acid, alginic acid, and their salts and derivatives. Examples of water-soluble vinyl polymers include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl methyl ether, poly N-vinylacetamide, polyacrylamide, and polyimide. Here, examples of the salt include alkali metal salts such as sodium salts, and ammonium salts. Examples of the derivative include esters such as alkyl esters, and ethers.
[0033] Among these thickeners, from the viewpoint of better dispersing CNTs in the resulting CNT dispersion, cellulose-based polymers, polyvinylpyrrolidone, and polyacrylic acid esters are preferred, and carboxymethylcellulose and its salts, polyvinylpyrrolidone, and polymethylacrylate are more preferred.
[0034] <<Weight average molecular weight>> The weight average molecular weight of the thickener is preferably 5000 or more, more preferably 10000 or more, and is preferably 1,000,000 or less, and more preferably 500,000 or less. If the weight average molecular weight of the thickener is 5000 or more, the dispersibility of CNTs can be improved. Also, if the weight average molecular weight of the thickener is 1,000,000 or less, an increase in the viscosity of the CNT dispersion can be suppressed. In the present invention, the "weight average molecular weight" can be measured using gel permeation chromatography and expressed as a standard polystyrene equivalent value.
[0035] <<Content ratio>> The proportion of the thickener contained in the mixed liquid is preferably 0.1% by mass or more, more preferably 0.4% by mass or more, preferably 2.0% by mass or less, and more preferably 1.2% by mass or less, based on 100% by mass of the total amount of the mixed liquid. Thus, if the content of the thickener in the mixed liquid is within the above range, the carbon nanotubes can be more satisfactorily dispersed in the obtained carbon nanotube dispersion, while the conductivity of the carbon film or the like produced using the carbon nanotube dispersion can be increased.
[0036] <Other ingredients> Other components that the mixed liquid may optionally contain include conductive materials other than CNTs, polymer components other than the above-mentioned thickeners, antioxidants, resins, etc. The mixed liquid may contain only one type of other component, or may contain two or more types.
[0037] The proportion of other components contained in the mixed liquid is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass (i.e., the mixed liquid does not contain other components), with the total amount of the mixed liquid being 100% by mass.
[0038] <<Wet Jet Mill>> Examples of wet jet mills that can be used for the dispersion treatment in the dispersion step include "Nanovata (registered trademark)" (manufactured by Yoshida Kikai Kogyo Co., Ltd.), "BERYU SYSTEM PRO" (manufactured by Biryu Co., Ltd.), ultra-high pressure wet micronization device (manufactured by Yoshida Kogyo Co., Ltd.), "Nanomizer (registered trademark)" (manufactured by Nanomizer Co., Ltd.), and "Starburst (registered trademark)" (manufactured by Sugino Machine Ltd.).
[0039] Here, examples of the nozzles equipped in the wet jet mill include a straight nozzle and a cross nozzle. The straight nozzle has an I-shaped nozzle cross section and requires relatively small processing energy. On the other hand, the cross nozzle has an X-shaped nozzle cross section and requires larger processing energy than the straight nozzle. From the viewpoint of dispersing CNTs more satisfactorily in the obtained CNT dispersion, it is preferable to use a straight nozzle as the nozzle equipped in the wet jet mill.
[0040] [pressure] The pressure applied to the mixture during dispersion processing using a wet jet mill must be 50 MPa or more. If the pressure applied to the mixture is less than 50 MPa, there is a risk that the CNTs cannot be dispersed well. From the viewpoint of more favorably dispersing the CNTs in the resulting CNT dispersion while suppressing the scission of the CNTs, the pressure applied to the mixture is preferably 55 MPa or more, and more preferably 150 MPa or less, and more preferably 100 MPa or less.
[0041] [Number of passes] The number of passes of the dispersion treatment using a wet jet mill must satisfy the relationship of the following formula (1). -0.15 × (pressure applied to the mixed liquid (MPa)) + 35 < number of passes < -1 × (pressure applied to the mixed liquid (MPa)) + 170 (1) If the number of passes does not satisfy the relationship of the above formula (1), there is a risk that the CNTs may not be dispersed well.
[0042] From the viewpoint of suppressing breakage of the carbon nanotubes and more favorably dispersing the carbon nanotubes in the resulting carbon nanotube dispersion, it is preferable that the number of passes satisfies the relationship of the following formula (2). -0.2 x (pressure applied to the mixed liquid (MPa)) + 45 ≦ number of passes ≦ -0.9 x (pressure applied to the mixed liquid (MPa)) + 150 (2)
[0043] Furthermore, from the viewpoint of suppressing breakage of the carbon nanotubes while more effectively dispersing the carbon nanotubes in the resulting carbon nanotube dispersion, the number of passes is preferably 80 or less, and more preferably 60 or less.
[0044] <Other processes> As another step, there may be mentioned a step (mixing step) of mixing CNTs, a solvent, and a thickener to obtain a mixed liquid before the above-mentioned dispersing step.
[0045] (CNT dispersion) The CNT dispersion is produced by the above-mentioned method for producing a CNT dispersion of the present invention. Therefore, the CNT dispersion contains at least a plurality of CNTs, a solvent, and a thickener, and optionally further contains components other than the CNTs, the solvent, and the thickener (other components). At least a part of the CNTs is preferably single-walled CNTs, and the CNTs form a CNT bundle in the CNT dispersion. In the present invention, the CNT bundle means a bundle formed by assembling a plurality of CNTs along the long axis direction of the CNTs.
[0046] <cnt> The CNTs are a dispersion of the raw CNTs contained in the mixed liquid described above, and the preferred properties and content ratio of the CNTs in the CNT dispersion liquid are similar to those of the raw CNTs in the mixed liquid described above in the section "Method of producing CNT dispersion liquid." Here, the CNT bundles in the CNT dispersion liquid preferably have the following properties:
[0047] [Average length of CNT bundle] The average length of the CNT bundle is preferably 1.5 μm or more, more preferably 1.7 μm or more, even more preferably 1.8 μm or more, even more preferably 1.9 μm or more, and particularly preferably more than 2.0 μm. If the average length of the CNT bundle is 1.5 μm, the CNTs can be well dispersed in the CNT dispersion. The upper limit of the average length of the CNT bundle is not particularly limited, and can be, for example, 3.5 μm or less, or 3.0 μm or less. In the present invention, the "average length of the CNT bundles" can be measured by the method described in the Examples.
[0048] [Average diameter of CNT bundles] The average diameter of the CNT bundle is preferably 0.0180 μm or less, more preferably 0.0170 μm or less, and even more preferably less than 0.0160 μm. If the average diameter of the CNT bundle is 0.0180 μm or less, the CNTs can be well dispersed in the CNT dispersion liquid. The lower limit of the average diameter of the CNT bundle is not particularly limited, and can be, for example, 0.0120 μm or more, and can be 0.0125 μm or more. In the present invention, the average diameter of the CNT bundles can be measured by the method described in the Examples.
[0049] [Average aspect ratio of CNT bundles] The average aspect ratio of the CNT bundle is preferably more than 93.75, more preferably 100 or more, even more preferably 120 or more, and particularly preferably 150 or more. If the average aspect ratio of the CNT bundle is more than 93.75, the CNTs can be well dispersed in the CNT dispersion. The upper limit of the average aspect ratio of the CNT bundle is not particularly limited, and can be, for example, 250 or less, 225 or less, or 200 or less.
[0050] <Solvents, thickeners, and other ingredients> The solvent, thickener, and other components contained in the CNT dispersion are those contained in the mixed liquid described above, and the preferred properties and content ratios, etc. of these components in the CNT dispersion are the same as the preferred properties and content ratios, etc. of these components in the mixed liquid described above in the section "Method of producing CNT dispersion". EXAMPLES
[0051] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In the examples and comparative examples, the average length, average diameter, and average aspect ratio of the CNT bundles, as well as the G / D ratio of the CNTs, were evaluated by the following methods.
[0052] <Average length, average diameter, average aspect ratio> The CNT dispersions prepared in the examples and comparative examples were diluted to a concentration of single-walled CNT of 25 mass ppm. It was diluted with pure water so as to become. After dropping one drop of the obtained diluted solution onto the wafer with a dropper, the wafer was placed on a hot plate heated to 90 °C and baked for 1 minute. The obtained CNT-coated wafer was observed using a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, product name "SU8200") under the conditions of a working distance of 3 mm, an acceleration voltage of 1.0 kV, and a magnification of 10,000 times, and a plurality of SEM images containing 10 or more CNTs in the field of view were acquired. For 100 CNT bundles arbitrarily extracted from the acquired SEM images, the diameter (outer diameter) and length of the bundles were measured. Then, the arithmetic mean value of the diameters of the 100 measured CNT bundles was taken as the average diameter (μm) of the CNT bundles in the CNT dispersion. Also, the arithmetic mean value of the lengths of the 100 measured CNT bundles was taken as the average length (μm) of the CNT bundles in the CNT dispersion. The average aspect ratio was calculated by dividing the average length (μm) by the average diameter (μm). Then, the average length of the CNT bundles and the average diameter of the CNT bundles were evaluated according to the following criteria. A CNT dispersion in which the average length of the CNT bundles is 1.5 μm or more (i.e., the evaluation is B or more) and the average diameter of the CNT bundles is 0.0180 μm or less (i.e., the evaluation is B or more) has excellent dispersibility of CNTs. [Average length of CNT bundles] A: More than 2.0 μm B: 1.5 μm or more and 2.0 μm or less C: Less than 1.5 μm or unmeasurable length [Average diameter of CNT bundles] A: Less than 0.0160 μm B: 0.0160 μm or more and 0.0180 μm or less C: More than 0.0180 μm or unmeasurable length <G / D ratio> Using a microscopic laser Raman spectrophotometer (manufactured by Thermo Fisher Scientific, product name "Nicolet Almega XR"), the Raman spectra of the CNTs used in the examples and comparative examples were measured. Then, for the obtained Raman spectra, the intensity of the G-band peak observed in the vicinity of 1590 cm -1 and the intensity of the peak near 1340 cm -1 The intensity of the D-band peak observed in the vicinity was determined, and the G / D ratio was calculated.
[0053] (Example 1) (Preparation of CNT Dispersion) To 300 mL of an aqueous solution containing sodium carboxymethyl cellulose (average degree of polymerization = 500; manufactured by Tokyo Chemical Industry Co., Ltd.) as a thickener in water as a solvent (concentration of sodium carboxymethyl cellulose: 0.4% by mass), 1.2 g of CNTs (single-walled CNTs, G / D ratio: 1.2, referred to as "CNT-a") produced by the method described in Example 4 of International Publication No. 2022 / 114237 was added to obtain a mixed solution (concentration of single-walled CNTs: 0.4% by mass). For this mixed solution, using a wet jet mill (manufactured by Yoshida Kikai Kogyo Co., Ltd., model number "NVL-ES008A-D10", product name "Nano Veyta (registered trademark)"), dispersion treatment was performed under the conditions of a pressure of 50 MPa and a number of passes of 35 times. Specifically, while applying back pressure, a shear force was applied to the mixed solution to disperse the single-walled CNTs, and a CNT dispersion was obtained. Then, the average length, average diameter, and aspect ratio of the CNT bundles in the obtained CNT dispersion were measured to evaluate the dispersibility of the CNTs. The results are shown in Table 1.
[0054] (Examples 2 to 10) When preparing the CNT dispersion, the CNT dispersion was prepared in the same manner as in Example 1 except that the pressure and the number of passes of the dispersion treatment by the wet jet mill were changed as shown in Table 1. Then, the evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.
[0055] (Examples 11 to 14) When preparing the CNT dispersion, the CNT dispersion was prepared in the same manner as in Example 1 except that the content ratio of the thickener in the mixed solution was changed from 0.4% by mass to 0.8% by mass and the number of passes of the dispersion treatment by the wet jet mill was changed as shown in Table 1. Then, the evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.
[0056] (Examples 15 to 18) A CNT dispersion was prepared in the same manner as in Example 1, except that the content of the thickener in the mixed liquid was changed from 0.4% by mass to 1.2% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Tables 1 and 2. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Tables 1 and 2.
[0057] (Example 19) A CNT dispersion was prepared in the same manner as in Example 1, except that polymethyl acrylate was used as the thickener instead of carboxymethyl cellulose and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 2. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Table 2.
[0058] (Example 20) A CNT dispersion was prepared in the same manner as in Example 1, except that polyvinylpyrrolidone was used instead of carboxymethylcellulose as the thickener during preparation of the CNT dispersion, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 2. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Table 2.
[0059] Example 21 During preparation of the CNT dispersion, single-walled CNT (manufactured by Zeon Corporation, product name "ZEONANO (registered trademark) SG101", G / D ratio: 5.0, referred to as "CNT-b") was used instead of CNT-a, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 2. Except for this, a CNT dispersion was prepared in the same manner as in Example 1. Evaluation was then performed in the same manner as in Example 1. The results are shown in Table 2.
[0060] Example 22 During preparation of the CNT dispersion, single-walled CNT (manufactured by OCSiAl, product name "Tuball" (registered trademark), G / D ratio: 109) was used instead of CNT-a, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 2. Except for this, the CNT dispersion was prepared in the same manner as in Example 1. Evaluation was then performed in the same manner as in Example 1. The results are shown in Table 2.
[0061] (Example 23) When preparing the CNT dispersion, single-walled CNTs produced by the eDIPS method (manufactured by Meijo Nano Carbon Co., Ltd., product name "MEIJO eDIPs (registered trademark), G / D ratio: 119) were used instead of CNT-a, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 2. Except for this, the preparation of the CNT dispersion was carried out in the same manner as in Example 1. Then, evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.
[0062] (Examples 24 to 29) A CNT dispersion was prepared in the same manner as in Example 1, except that the CNT content in the mixed liquid was changed from 0.4% by mass to 0.2% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Tables 2 and 3. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Tables 2 and 3.
[0063] (Examples 30 to 34) A CNT dispersion was prepared in the same manner as in Example 1, except that the CNT content in the mixed liquid was changed from 0.4% by mass to 0.1% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 3. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Table 3.
[0064] (Comparative Examples 1 to 9, 12 to 23) A CNT dispersion was prepared in the same manner as in Example 1, except that the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Tables 3 to 5. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Tables 3 to 5.
[0065] (Comparative Examples 10 to 11) A CNT dispersion was prepared in the same manner as in Example 1, except that the content of the thickener in the mixed liquid was changed from 0.4% by mass to 0.8% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 4. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Table 4.
[0066] (Comparative Examples 24 to 25) A CNT dispersion was prepared in the same manner as in Example 1, except that the content of the thickener in the mixed liquid was changed from 0.4% by mass to 1.2% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 4. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Table 4.
[0067] (Comparative Examples 26 to 34) A CNT dispersion was prepared in the same manner as in Example 1, except that the CNT content in the mixed liquid was changed from 0.4% by mass to 0.2% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Table 5. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Table 5.
[0068] (Comparative Examples 35 to 41) A CNT dispersion was prepared in the same manner as in Example 1, except that the CNT content in the mixed liquid was changed from 0.4% by mass to 0.1% by mass, and the number of passes of the dispersion treatment using a wet jet mill was changed as shown in Tables 5 and 6. Then, an evaluation was performed in the same manner as in Example 1. The results are shown in Tables 5 and 6.
[0069] (Comparative Example 42) During preparation of the CNT dispersion liquid, a mixed liquid was prepared as described below, and a dispersion treatment was performed on the mixed liquid, but other than that, the CNT dispersion liquid was prepared in the same manner as in Example 1. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 6. <Preparation of mixed liquid and dispersion treatment> A 900 mL M sample bottle was charged with 300 mL of an aqueous solution (concentration of sodium carboxymethylcellulose: 0.4 mass%) containing sodium carboxymethylcellulose (average degree of polymerization = 500; manufactured by Tokyo Chemical Industry Co., Ltd.) as a thickener in water as a solvent, and 1.2 g of CNT-a as single-walled CNTs to prepare a mixed solution. The mixed solution was then subjected to a dispersion treatment at an amplitude of 50% for 1 minute using an ultrasonic homogenizer (Advanced Digital Sonifer (registered trademark), MODEL450DA, manufactured by BRANSON Corporation) to prepare a CNT dispersion solution.
[0070] In addition, in Tables 1 to 6 shown below, "CMC" stands for sodium carboxymethylcellulose; "PMA" stands for polymethyl acrylate. "PVP" refers to polyvinylpyrrolidone. [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6]
[0071] The results shown in Figures 1 to 3 and Tables 1 to 6 show that in Examples 1 to 34, in which the pressure applied to a mixed liquid containing carbon nanotubes, a solvent, and a thickener and the number of times the mixed liquid is passed through the wet jet mill satisfy predetermined conditions when the mixed liquid is subjected to a dispersion process using a wet jet mill, CNTs can be well dispersed in the resulting CNT dispersion liquid. In the graphs of FIGS. 1 to 3, the lower straight line is the number of passes (vertical axis)=-0.15×pressure (horizontal axis)+35, and the upper straight line is the number of passes (vertical axis)=-1×pressure (horizontal axis)+170. [Industrial Applicability]
[0072] According to the present invention, it is possible to provide a method for producing a carbon nanotube dispersion liquid in which carbon nanotubes are well dispersed.< / cnt> < / cnt>
Claims
1. The method includes a step of subjecting a mixed liquid containing carbon nanotubes, a solvent, and a thickener to a dispersion treatment using a wet jet mill, The pressure applied to the mixture in the dispersion treatment is 50 MPa or more; The method for producing a carbon nanotube dispersion liquid, wherein the number of passes in the dispersion treatment satisfies the relationship of the following formula (1): −0.15×(pressure applied to the mixed liquid (MPa))+35<number of passes<−1×(pressure applied to the mixed liquid (MPa))+170...(1)
2. The method for producing a carbon nanotube dispersion liquid according to claim 1 , wherein the number of passes in the dispersion treatment satisfies the relationship of the following formula (2): −0.2×(pressure applied to the mixed liquid (MPa))+45≦number of passes≦−0.9×(pressure applied to the mixed liquid (MPa))+150... (2)
3. The method for producing a carbon nanotube dispersion liquid according to claim 1 , wherein the number of passes in the dispersion treatment is 60 or less.
4. The method for producing a carbon nanotube dispersion liquid according to claim 1 , wherein a pressure applied to the mixture liquid in the dispersion treatment is 100 MPa or less.
5. The method for producing a carbon nanotube dispersion liquid according to claim 1 , wherein a content of the carbon nanotubes in the mixed liquid is 0.4% by mass or more and 1.0% by mass or less.
6. The method for producing a carbon nanotube dispersion liquid according to claim 1 , wherein a content ratio of the thickener in the mixed liquid is 0.4 mass % or more and 1.2 mass % or less.
7. The method for producing a carbon nanotube dispersion liquid according to claim 1 , wherein the thickener is carboxymethyl cellulose or a salt thereof.
8. The method for producing a carbon nanotube dispersion liquid according to any one of claims 1 to 7, wherein the carbon nanotubes have a G / D ratio of 0.5 or more and 120 or less.
Citation Information
Patent Citations
Formation of monolayer carbon nanotube coating and monolayer carbon nanotube coating formed thereby
JP2000086219A
Carbon nanotube dispersion and usage therefor
WO2020004095A1